Triboelectric nanogenerator based on tin doped zinc oxide and polyvinyl alcohol composite thin film for energy harvesting applications - Dayana Kamaruzaman; Mohamad Hafiz Mamat; Anees Abdul Aziz; A Shamsul Rahimi A Subki; Nurul Izzati Kamal Ariffin; Nurul Syafiqah Mohamed Mustakim; Norfarariyanti Parimon; N. Vasimalai; Mohd Hanapiah Abdullah; Nor Diyana Md Sin; Mohd Khairul Ahmad; Suriani Abu Bakar; et al. (Semarak Ilmu Publishing, 2025)
The triboelectric nanogenerator (TENG) collects mechanical energy from its surroundings and converts it to electrical signals that can be used in sustainable energy harvesting technologies to help maintain the social ecosystem. However, TENG operation with pure triboelectric material may not be sufficient to power a small electronic system without modification. The optimal material capable of producing significant electrical energy with flexible structures remains a major barrier to practical application. In this study, tin-doped zinc oxide (Sn:ZnO) and polyvinyl alcohol (PVA) composite thin films were prepared using a simple solution immersion technique at various Sn atomic percentage (at.%) concentrations for use in TENG devices. The crystalline quality of a composite thin film made of Sn:ZnO and PVA was identified using x-ray diffraction. The microstructure changes of the composite thin film were found to be influenced by Sn doping, as studied using optical microscopy. The TENG with 2.5 at.% Sn:ZnO/PVA composite thin film and Kapton film achieved the highest peak voltage of 8.5 V in open circuit and 90 µW output power at 1 MΩ. The produced electrical output was then used to store energy in capacitors. According to its TENG properties, the Sn:ZnO/PVA composite thin film-based TENG has the potential to be used in low power electronic devices.